THE ROLE OF ENGLISH PROVERBS IN THE DEVELOPMENT OF WRITING SKILL - Sudiran Sudiran (Celt: A Journal of Culture, English Language Teaching & Literature, 2007)
Writing ability plays all importallt role ill the students' academic life. Students' activities cannot be separated from writing. They have to write projects. propose a research. write a research report. etc. Writing ability enables students to disseminate information and new findings. This study aims (1) to describe the use of English proverbs to enhance the students writing achievement. (2) to reveal students' competence to write a purposive paragraph. (3) to describe the students' response to the use of the English proverbs in writing skill. The result of the study shows that (1) English proverbs can be considered as statement containing moral values. English proverbs call be used as teaching aids in teaching writing. (2) English proverbs enable lecturers to promote students' writing ability. This fact can be supported by the result of students' writing test that is 74.62. which can be categorized into a good category, such as proposed by Hartfiel et. al's Learning ESL Composition. (3) Based on the students' response, generally they have positive attitudes toward the use of English proverbs because it can help them to increase their writing ability. Moreover, English proverbs enable students to elaborate their ideas in writing a paragraph.